Excessive Daytime Sleepiness among Dental Students - A Systematic Review and Meta-Analysis - Jorge H. Wilches-Visbal; Alex A. Angulo-Luna; Adalberto Campo-Arias (Indian Journal of Dental Research)
Excessive daytime sleepiness is highly prevalent and variable in health students. However, a meta-analysis that synthesises the prevalence of this symptom in dental students has yet to be reported. This review aimed to compute the pooled prevalence of sleepiness in dental students. A systematic review and meta-analysis of studies published between 2000 and 2023 was developed in Spanish, English, and Portuguese. The keywords were sleepiness, excessive drowsiness, Epworth scale for sleepiness, and dental students in all three languages. Original articles and degree theses that reported the frequency of sleepiness with a cut-off point for the Epworth scale for sleepiness greater than 10 were included. The sample sizes and the number of students positive for sleepiness were observed, and the prevalence, raw and adjusted for sample size, was calculated. Seven articles were included with participant samples between 128 and 325 students, totalling 1,546. Students were positive on the Epworth scale for sleepiness between 43 and 189, with a sum of 671. The prevalences were between 22.7% and 58.4%; the pooled prevalence was 42.7% (95% CI: 40.3–45.2). In conclusion, sleepiness was present in 4 out of 10 dental students. It is necessary to systematise the factors associated with sleepiness and establish a relationship with the academic performance of dental students.